Wave Propagation - Ferrarese, Giorgio; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
Lectures: A. Jeffrey: Lectures on nonlinear wave propagation.- Y. Choquet-Bruhat: Ondes asymptotiques.- G. Boillat: Urti.- Seminars: D. Graffi: Sulla teoria dell$1 (Bottica non-lineare.- G. Grioli: Sulla propagazione del calore nei mezzi continui.- T. Manacorda: Onde nei solidi con vincoli interni.- T. Ruggeri: "Entropy principle" and main field for a non linear covariant system.- B. Straughan: Singular surfaces in dipolar materials and possible consequences for continuum mechanicss
Lectures: A. Jeffrey: Lectures on nonlinear wave propagation -- Y. Choquet-Bruhat: Ondes asymptotiques -- G. Boillat: Urti -- Seminars: D. Graffi: Sulla teoria dell$1 (Bottica non-lineare -- G. Grioli: Sulla propagazione del calore nei mezzi continui -- T. Manacorda: Onde nei solidi con vincoli interni -- T. Ruggeri: "Entropy principle" and main field for a non linear covariant system -- B. Straughan: Singular surfaces in dipolar materials and possible consequences for continuum mechanics.s
Keywords: Mathematics; Differential equations, partial; Mathematics; Partial Differential Equations